Neonatal Outcomes of Pregnancies Complicated By Maternal Hyperthyroidism - Mamat @ Abdullah, Adlina Awanis (2021)
Objective: We aim to study the proportion of infants born to maternal hyperthyroidism, their clinical, hormonal status, median time and factors affecting time for serum free T4 (fT4) and TSH normalization. Methodology: A cross-sectional study recruited 186 inborns admitted to Neonatal Intensive Care Unit (NICU), Hospital Universiti Sains Malaysia (Hospital USM) from January 2013 until December 2018. We analyzed newborn’s demographic and clinical characteristic, maternal treatment, maternal thyroid autoantibodies level and thyroid function. Finally, we analyzed the newborn’s thyroid function and thyroid autoantibodies. Abnormal thyroid function was categorised according to European Society of Paediatric Endocrinology (ESPE) for newborn. Kaplan Meier analysis were used to determine median time of fT4, TSH normalization and multiple logistic regression model were used to examine the associations between risk variables affecting fT4, TSH normalization in these newborns. Results: The proportion of newborns with maternal hyperthyroidism were 0.92% (186/ 20198). Only 170 newborns were included in the study. Out of 102 (60%) newborns with an abnormal TFT, 7 (4.1%) developed overt hyperthyroidism with 4 (2.4%) were complicated by thyroid storm. Only 54 out 170 mothers (31.7%) were checked for presence of thyroid autoantibodies. The overall median time for TFT normalization was 30 days (95% CI): (27.1, 32.8). Cox Proportional Hazard revealed normal TFT on day 3-5, crude HR: 95% CI: 4.918 (2.11, 11.44) and day 15: 3.496 (1.61, 7.58) were significant variables affecting time of normalization. Conclusion: The proportion of newborns with maternal hyperthyroidism were 0.92%. Most infants with maternal hyperthyroidism had a self-limiting course with median TFT normalization time of 30 days. Abnormal TFT at day 3-5, abnormal TFT at day 15, maternal received thyroid treatment and maternal presence of thyroid autoantibodies were significant predictors affecting fT4, TSH normalization for these newborns.